Evaluating fibre orientation dispersion in white matter: comparison of diffusion MRI, histology and polarized light imaging - Mollink, Jeroen; Kleinnijenhuis, Michiel; Cappellen van Walsum, Anne-Marie van; Sotiropoulos, Stamatios N.; Cottaar, Michiel; Mirfin, Christopher; Heinrich, Mattias P.; Jenkinson, Mark; Pallebage-Gamarallage, Menuka; Ansorge, Olaf; Jbabdi, Saad; Miller, Karla L. (Elsevier, 2017)
Diffusion MRI is an exquisitely sensitive probe of tissue microstructure, and is currently the only non-invasive measure of the brain’s fibre architecture. As this technique becomes more sophisticated and microstructurally informative, there is increasing value in comparing diffusion MRI with microscopic imaging in the same tissue samples. This study compared estimates of fibre orientation dispersion in white matter derived from diffusion MRI to reference measures of dispersion obtained from polarized light imaging and histology.